Pengembangan Buku Ajar Akidah Akhlak Berbasis E-Book Story untuk Peningkatan Moral Reasoning Siswa - Mir’atus Sa’diyah; Esa Nur Faizah (CV. Gerasi Insan Nusantara, 2026)
Advancements in educational technology have increased demand for innovative digital learning materials that enhance conceptual understanding and foster students' moral reasoning. This study aimed to develop a